Evaluation of the effect of two types of fertilizer on the growth, development and productivity of Hydroponic Green Forage Oat (Avena sativa L.) and Ryegrass (Lolium multiflorum Lam.) as a biomass source (2016)
Hydroponic Green Forage (HGF) is increasingly being internationally recognized as an alternative to ensure sustainable biomass production per unit area in the shortest possible time and at the highest possible quality. This research thus evaluates the effect of two nutrient solutions (with two dilutions in each case) applied in the HGF production system for Oats and Ryegrass on the parameters of growth, development and productivity of both species. To this end, a handmade greenhouse was built in which two seed sowing trays were installed with a fertigation system for oats and ryegrass species. The experimental design consisted of the assembly of two modules of 24 seed trays in which HGF Oat and Ryegrass were grown using two nutrient solutions (which were applied according to the position of the seed trays inside the module at level 2 and level 4). The tests showed for the two species evaluated that the use of organic solutions significantly promote the conversion and yield variables of fresh mass per unit area - an increase in the relative growth rate, the net assimilation rate, the crop growth rate and the absolute growth rate; all of these as a measure of crop development. Likewise, when the analysis was conducted, it was observed that the most economic assemblies turned out to be those which used the liquid humus as nutrient solution to 1/20 v.v. and 1/40 v.v. This supports the conclusion that the use of organic nutrient solution can yield high quality HGF exceeding the development parameters of those produced using conventional (synthetic) nutrient solutions Copyright © 2016, AIDIC Servizi S.r.l.,.